The Improvement of Students’ Ability to Write Exposition Text through Learning Cycle Model - Roy Efendi; Emzir Emzir; Aceng Rahmat (STKIP Singkawang, 2018)
This research aims at improving students’ ability to write exposition text through learning cycle model to the third-semester students of Indonesian Language Study Program, Faculty of Teacher Training and Educational Sciences, Pakuan University. The method used for this research is action research with qualitative and quantitative approach. Qualitative data are taken from data analysis and analysis of learning process from three cycles. Meanwhile, quantitative data are taken from the comparison of students' score from the first to the third cycle. The implementation of learning cycle that consists of engagement, exploration, explanation elaboration and evaluation in writing exposition activity done in every cycle successfully improves students’ ability to write exposition text. It is shown on the average score which increases from 52.38 to 80.13. This improvement comes along the improvement of students’ activity in expressing their ideas throughout learning cycle. As a result, learning cycle can improve students’ ability to write exposition text.